Efforts To Improve Pkn Learning Achievement In Class XII SMA Negeri 3 Ambon By Applying Two Stay-Two Stray Engineering In Learning - Tahalele, A.R (Global Science Education Journal, 2019)
This research is a classroom action research, which aims to improve the Learning Achievement of Civics in Class XII Students of SMA Negeri 3 Ambon By Applying the Two Stay-Two Technique. The subjects in this study were students of Class XII  of SMA Negeri 3 Ambon with a total of 32 students The procedure of implementing CAR is presented in the form of a cycle (cycle) assessment process which is expressed in a PTK spiral. The PTK spiral actually describes cycle after cycle. One cycle consists of four main components of CAR, namely: action planning, action implementation, action observation, and reflection and revision of actions. an increase in the percentage of student activity during learning and an increase in the percentage of students who have finished learning, ie in cycle I the percentage of student activity is 57.50%, increasing in cycle II to 77.50%, and in cycle III increasing to 87.50%, while the percentage of the total number of students who completed study in the first cycle was 53.13%, increased in the second cycle to 71.88%, and in the third cycle increased to 87.50%.